Streams and the Milky Way dark matter halo. Issue Volume 14:Issue S353(2019) (June 2019) - Newberg, Heidi Jo; Shelton, Siddhartha; Mendelsohn, Eric; Weiss, Jake; Arsenault, Matthew; Bauer, Jacob S.; Desell, Travis; Judd, Roland; Magdon-Ismail, Malik; Newberg, Lee A.; Newby, Matthew; Rayment, Clayton; et al.
Abstract: We describe an algorithm that can fit the properties of the dwarf galaxy progenitor of a tidal stream, given the properties of that stream. We show that under ideal conditions (the Milky Way potential, the orbit of the dwarf galaxy progenitor, and the functional form of the dwarf galaxy progenitor are known exactly), the density and angular width of stars along the stream can be used to constrain the mass and radial profile of both the stellar and dark matter components of the progenitor dwarf galaxy that was ripped apart to create the stream. Our provisional fit for the parameters of the dwarf galaxy progenitor of the Orphan Stream indicates that it is less massive and has fewer stars than previous works have indicated.